Tourism Carrying Capacity of Coastal Ecosystems on Ketawai Island, Central Bangka, Indonesia - Sujadi Priyansah; Erny Poedjirahajoe; Lies Rahayu Wijayanti Faida (Journal of Sylva Indonesiana, 2026)
Ecotourism development, especially in Central Bangka Island of Ketawai more rapidly. The rapid tourist activities on the Island of Ketawai can cause loss of quality attractions for damage to the ecosystem. This is because the pressure on the environment caused by the increased number of tourists. This study aims to determine the  maximum capacity rating  with ratings of three aspects:  (1) the carrying  capacity  of  the  region  (DDK),  (2)  the  carrying  capacity  of  the environment (the carrying capacity of the physical / PCC and the carrying capacity of the real / RCC), and (3) ecological carrying capacity (AR). This  study  uses  primary  data  by  direct  observation  in  the  field  and secondary data from relevant agencies. An assessment of the carrying capacity of the region (DDK), an assessment of the carrying capacity of the environment using methods the Physical Carrying Capacity (PCC), the carrying capacity of the Real (RCC), and an assessment of the ecological carrying capacity (AR). The  results  obtained,  there  are  two  tourist  activity  on  the  island  of Ketawai are picnic and camping. The result of the carrying capacity of the region (DDK) for picnic activities is 240 people / day and camping activities is 900 people/day. The  results  of the  physical  carrying  capacity (PCC)  for  picnic activities is 249 people / day and for camping is 100 people / day. Assessment of the real carrying capacity (RCC) for picnic activities is 239 people / day and camping 96/day. Ecological carrying capacity assessment. (AR) obtained the results of 81 people / day for a picnic and activity type 43 / day for camping activities. The value of these calculations are still well above the actual number of tourists who currently account for 9 person / day. Attraction Development Ketawai Island can still be optimized however, by taking into account the balance and sustainability of the local environment.